Prinsip Pembelajaran Kurikulum Merdeka (Tinjauan Holistik Paradigma Ki Hajar Dewantara Sebagai Pendekatan) - Hasibuan, Akmal Rizki Gunawan; Amalia, Assyifa; Resky, Muhammad; Adelin, Nur; Muafa, Novaldi Fadil; Zulfikri, Muhammad Adhi (LPPM Institut Pendidikan Nusantara Global, 2024)
Merdeka Curriculum is a curriculum designed to provide flexibility to education units in developing learning according to the needs and characteristics of students. This curriculum carries a number of learning principles that are different from the previous curriculum. This study aims to analyse the learning principles of the Merdeka Curriculum using the holistic approach of Ki Hajar Dewantara's paradigm. The method used in this research uses descriptive qualitative with a literature review approach. The data analysis technique starts from collecting data related to various topics that are the same as the article being studied, reducing data to produce data that is in line with research questions, and presenting data to draw conclusions. The results of this study show that Ki Hajar Dewantara's thoughts in the principles of learning based on the Merdeka Curriculum are flexibility, depth, relevance, interactive, and empowerment. Ki Hajar Dewantara's paradigm approach emphasises the importance of learner-centred education, active and meaningful learning, and the development of learners' characters and competencies. This research also contributes to the development of education in Indonesia by highlighting the importance of active learner engagement, contextualised learning, subject integration, character development and independence in learning. In addition, this research also identifies internal and external barriers to the implementation of Merdeka Curriculum, and emphasises the need to overcome these barriers so that the implementation of Merdeka Curriculum can run well.